Analisis Strategi Peningkatan Pelayanan Dinas Penanggulangan Kebakaran dan Penyelamatan Provinsi DKI Jakarta - Fajar Maulana; Eka Rofiyanti (Institut Ilmu Sosial dan Manajemen Stiami, 2026)
Public services are provided by the government, private sector, or public bodies, with or without payment for the needs and/or interests of citizens, one of which is the service provided by the Technical Implementation Unit of the Fire Department. This study aims to evaluate the service improvement strategy of the DKI Jakarta Provincial Fire and Rescue Department. This study uses a qualitative descriptive approach. Primary data used in this study are the results of interviews with informants. The results show that the DKI Jakarta Provincial Fire and Rescue Department has demonstrated a clear strategy in community-based fire prevention, with fairly structured directions and actions. However, challenges such as limited human resources, bureaucracy, and suboptimal organizational learning still need to be addressed. Data-based evaluation and innovation must be strengthened so that the implemented strategy is more adaptive and sustainable. Obstacles that occur include: Inequality in Program Implementation, Slow Bureaucracy and Complex Administration, Less Reflective Evaluation and Suboptimal Data and Technology Integration. The solutions offered are: Community Empowerment Through RW Siaga Api, Technology-Based Training and Micro-Targeting Counseling, Optimization of Digital Communication and Resident Coordination Groups, Budget Increase and Procedure Simplification, Utilization of Evaluation as a Strategic Learning Resource Cross-Agency and Community Collaboration Several programs have also begun to collaborate with local communities, RT/RW administrators, and institutions such as PLN and BPBD in joint campaigns and simulations. This collaboration expands networks and strengthens social bases. Keywords: Strategy; Service; Fire; Disaster Management; Rescue